Digitalization of Mortgage Lending Process in India - Bindal, Neeraj (Digital Repository of Theses, 2025)
The digitalisation of mortgage lending in India transforms the financial sector by addressing loan management issues like efficiency, transparency, and client experience. Digital technologies can overcome traditional obstacles and accelerate expansion in India's housing and real estate sector, which relies on mortgage lending. Purpose/Objective The primary goal of this study is to develop a model based on the Unified Theory of Acceptance (UTAUT) to examine the acceptance of the digitalization of mortgage process in India. The results of this study will be valuable to financial institutions, policymakers, and technology providers to better understand the effectiveness of digital mortgage platforms and how they can further improve operational efficiencies, customer satisfaction, and financial inclusion in the Indian mortgage sector. Methodology/Approach This study uses a quantitative research approach to methodically look at the elements affecting digitalization of mortgage loans in India. The quantitative method makes it possible to gather and statistically examine numerical data, therefore helping to identify links among the variables of interest. Findings/Results The findings revealed that performance expectancy, effort expectancy, social influence, and facilitating conditions significantly contribute to users' intention to adopt digitalized mortgage solutions. Among these, social influence and effort expectancy emerged as the most influential factors, underscoring the importance of perceived benefits in motivating users to embrace digital platforms for mortgage processing. Significance/Implications Digitalisation could improve mortgage lending ecosystem decision-making, operational efficiency, and customer happiness, according to the research. The study emphasises stakeholder collaboration to solve problems and promote innovation. Conclusions This study systematically examined the factors influencing the adoption of digitalization in mortgage loans in India using the Unified Theory of Acceptance and Use of Technology (UTAUT) model, augmented with trust and anxiety constructs. The findings revealed that performance expectancy, effort expectancy, social influence, and facilitating conditions significantly contribute to users' intention to adopt digitalized mortgage solutions. Among these, social influence and effort expectancy emerged as the most influential factors, underscoring the importance of perceived benefits in motivating users to embrace digital platforms for mortgage processing. Limitations The study's dependence on current data and concentration on India limit its conclusions, highlighting the necessity for comparative studies across countries and marketplaces. Recommendations/Future Research Future study should expand the user base with rural background and user other non-English languages to collect the data as that will improve the sample size in Indian context. Additionally, Digital mortgage solutions' socio-economic effects should be studied longitudinally to better understand this subject. Also, future studies should focus on the adoption of emerging technologies such as quantum computing and advanced predictive analytics.